PROBLEMS AND PROSPECTS OF IMPLEMENTATION OF CLUSTER INITIATIVES IN THE TOURIST-RECREATIONAL COMPLEX OF THE NORTH-CAUCASIAN FEDERAL DISTRICT - N. V. Medyanik (Современная наука и инновации)
The article proves the thesis of the objective conditionality of the cluster approach in tourism and territorial development; about the effectiveness and unavoidable regularities of formation of clusters in tourism abroad, as well as the need for adaptation of such forms in national practices; about the contradictions in the implementation of cluster initiatives in tourism of the North-Caucasian region.